On mandantory activation of welfare receivers - Matz Dahlberg; Kajsa Johansson; Eva Mörk (Uppsala University, Department of Economics, 2008)
This paper investigates whether mandatory activation programs for welfare receivers have effects on welfare participation, employment and disposable income. In contrast to earlier studies we are able to capture both entry and exit effects. The empirical analysis makes use of a Swedish welfare reform in which the city districts in Stockholm gradually implemented mandatory activation programs for individuals on welfare. The reform is well suited for investigating effects of such programs for several reasons. First, the reform was not combined with any other policy instruments, like time limits or tax credits, making sure that we will capture effects of mandatory activation policies and nothing else. Second, the reform was initiated at different points of time in different city districts, which ease identification. Third, using data from city districts within a single local labor market we can control for confounding macro economic shocks. Overall, we find that mandatory activation of welfare receivers reduce overall welfare participation and increases employment. We also find that mandatory activation programs appear to work best for young people and for people born in non-Western countries. For disposable income, we do not find a statistically significant effect.
urn:nbn:se:uu:diva-86713
Keywords: I38; H31; 330; Welfare reform; Mandatory activation programs; Welfare participation; Employment; Difference-in-differences; Sozialhilfeempfänger; Aktivierende Sozialhilfe; Wirkungsanalyse; Städtischer Arbeitsmarkt; Stockholm; Schweden